Helicopter autopilot fly-away mode after loss of engine - Majori, E.; Cinquegrana, A.; Zaccuri, R.C.; Di Cintio, F.; Beseli, S.; Shields, C.; Laranjeiro, R.; Clough, K. (My University, 2017)
Without doubt, one of the biggest concerns during helicopter Search and Rescue operations is the possibility of engine failure whilst hovering at low height over the sea which can, in extreme cases, lead to the loss of the aircraft and crew. A successful Fly-Away manoeuvre can prevent unnecessary ditching; however, an optimised Fly-Away profile is difficult to manually perform with any degree of consistency. This paper addresses the design and implementation of an Autopilot Automatic Fly-Away Mode (FLYAW) to be used in a multi-engine aircraft following loss of one engine. The target platform is the AW101-612 helicopter and the fundamental objectives of the FLYAW Mode are: ? reduction in the delay time to initiate the Fly-Away in response to the engine failure; ? improved consistency and repeatability in execution of the Fly-Away technique; ? reduced pilot workload; ? to maintain the Fly-Away manoeuvre height loss within the published figures for manual execution of the technique. A simulation and flight test study has been undertaken to assess the FLYAW Mode in operation at a wide range of initial conditions. The conclusions from these activities are that the fundamental objectives have been accomplished. The mode brings enormous benefits that directly impact aircrew safety and reduce the probability of unnecessary aircraft ditching.